Mechanisms involved in reactive flotation of dolomite. - Midany, El
Dolomite impurities are increasing in the currently mined phosphate deposits in Florida. Several research efforts have been conducted in various laboratories around the globe to find methods to economically removing the dolomite. However, a universal and cost-effective process is not now in commercial use. In this paper, a new process for dolomite/apatite separation is presented. The different solubility of dolomite in slightly acidic solution is utilized to generate micro CO2 bubbles at the dolomite/water interface. Particle (dolomite)/bubble aggregates float to the surface leaving phosphate concentrate with low MgO content. Interestingly, up to 6.0 mm particles can be floated by such micro-bubble/particle aggregates. Different surface-active agents were tested to stabilize the bubbles. Results of these tests are presented, and the mechanisms involved are discussed.
Keywords: Dolomite; Apatite; Polyvinyl alcohol